Drivers of Productivity in Southeast Asia: People, Wellness, and Tech - Risky Angga Pramuja; Al Fauzi Rahmat; Supiandi; Yusnaidi (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study investigates how human capital, well-being support, and technology acceptance influence employee productivity inSoutheast Asia. Drawing on Human Capital Theory, the Job Demands-Resources model, and the UTAUT framework, data were collected from 480 employees across five countries. Structural Equation Modeling revealed that education level, skill development, health spending, and work-life balance significantly enhance work engagement and job satisfaction, which in turn drive productivity. Technology acceptance also emerged as a key enabler, influencing both motivation and performance. Mediation analysis confirmed the psychological pathways linking resources to outcomes, while multi-group analysis identified structural differences across national contexts. These findings underscore the need for localized strategies and integrated HR interventions. The study contributes to theory by linking structural and psychological drivers within a unified model and offers practical insights for policymakers and organizational leaders aiming to optimize productivity in rapidly developing and digitally transforming economies.